Front Cover: Electrochemical and Morphological Characterization of Zn−Al−Cu Layered Double Hydroxides as a Negative Electrode in Aqueous Zinc‐Ion Batteries (ChemElectroChem 15/2018). Issue 15 (9th July 2018) - Bani Hashemi, A.; Kasiri, G.; Glenneberg, J.; Langer, F.; Kun, R.; La Mantia, F.
Abstract : The Front Cover shows how layered double hydroxides can contribute to the improvement of the performances of the zinc anode in aqueous zinc‐ion batteries for the short‐term storage of renewable energies. More information can be found in the Article by A. Bani Hashemi and co‐workers onpage 2073 in Issue 15, 2018 (DOI:10.1002/celc.201800291 ).